Effective Supervision Model for Thai Language Learning Activity of Private Elementary Schools - Pongsri, Samart; Ruangmontri, Karn (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to develop an effective supervision model for Thai language learning activity of elementary schools and to evaluate by using the effective supervision model for Thai language learning activity. The findings were found that the effective supervision model for Thai language learning activity of elementary schools consists of 5 major elements, which are principle of the model; purpose of the model; and the effective supervision model with 6 stages, namely the study of current conditions, learning activities, supervision planning, supervision performance, reflection, and evaluation. The evaluation of the model and achievement condition of the model application, the evaluation of appropriateness, feasibility and usefulness were at the highest level. The evaluation of applying the effective supervision model for Thai language learning activity of private elementary schools revealed that the teachers had higher knowledge and understanding of effective leaning activities than before provided the supervision with the developed model. In addition, they also had higher competency of effective Thai language learning activity than before provided the supervision with the developed model. The supervisor gained higher competency of the effective supervision model for Thai language learning activity and related persons had satisfaction towards the effective supervision model for Thai language learning activity of private elementary schools at the highest level.